Testing the Structure-Conduct-Performance Paradigm for the Turkish Banking Sector: 2008-2013 - Celik, Tuncay; Kaplan, Muhittin (International Journal of Economics and Financial Issues, 2016)
The history of the studies on traditional industrial economics goes back to 1940’s. These studies (Mason, 1939; Bain, 1952) were in general conducted to provide information about market structure. The structure-conduct-performance (SCP) approach stemmed from these studies argues that, in the case of hindered market entry, the higher the concentration ratio and collusion among firms, the lower the level of competition in the market. Later on, a number of authors have contributed to the traditional SCP approach to improve it in a number of ways: the first hypothesis is called “the collusion hypothesis” and developed by Bain (1952); the second one was due to Demsetz (1973) and called the “efficient structure hypothesis”. This study aims at testing the applicability of the SCP approaches using the data related to 23 Turkish commercial banks operating over the period 2008-2013. The empirical results have shown that the modified efficient structure hypothesis holds for the Turkish banking sector over the sample period. Keywords: SCP, efficiency, concentration, Turkish banking JEL Classification: G21